Separator, electrochemical device, and electronic device

By using a separating film with Young's modulus between 52MPa and 90MPa in an electrochemical device, the film contains the first coating of polydopamine and binder polymer, the problem of insufficient fast charging performance and stability of secondary batteries in low temperature environments is solved, and the high temperature mechanical properties are improved.

CN119651064APending Publication Date: 2025-03-18NINGDE AMPEREX TECHNOLOGY LTD

Patent Information

Application Number
CN202510181104.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The secondary battery has insufficient fast charging performance and stability in low-temperature environments, and its mechanical performance is poor under high-temperature conditions. In particular, the negative electrode is prone to lithium dendrites, which affects the safety and service life of the battery.

Method used

An isolation film is used, which includes a base film and a first coating disposed on at least one side of the base film, the first coating consisting of polydopamine and a binder polymer, and the Young's modulus of the base film is between 52MPa and 90MPa. The isolation film improves the low-temperature fast charging performance and structural stability of the electrochemical device by promoting the rapid transmission of lithium ions and improving mechanical strength.

Benefits of technology

It effectively reduces the swelling of the isolation membrane in the electrolyte, improves the low-temperature fast charging performance and structural stability of the electrochemical device, extends the cycle life of the battery, and improves the high-temperature intermittent cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses an isolating membrane, an electrochemical device and an electronic device. The isolating membrane comprises a base membrane and a first coating arranged on at least one side of the base membrane, the first coating comprises polydopamine and an adhesive polymer, and the Young modulus of the base membrane is 52-90 MPa. The isolating membrane has good structural stability and relatively high mechanical strength, and the reduction of the strength of the isolating membrane after the isolating membrane is dissolved in an electrolyte and swells can be effectively reduced, so that the quick charging performance and the structural stability of an electrochemical device at a low temperature are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to an isolation membrane, an electrochemical device and an electronic device. Background Art

[0002] Secondary batteries are batteries that can be reused through the discharge process and reverse charging process of converting chemical energy into electrical energy, and are also one of the main directions of current energy storage research and development.

[0003] As the application scenarios become more diverse, higher requirements are placed on the fast charging performance and stability of secondary batteries in low temperature environments, as well as their mechanical properties under extreme conditions such as high temperatures. In particular, lithium dendrites are easily generated at the negative electrode of secondary batteries in low temperature environments, and this problem needs to be solved urgently. Summary of the invention

[0004] The present application provides an isolation membrane, an electrochemical device and an electronic device. The isolation membrane has good structural stability and high mechanical strength, and can effectively reduce the swelling of the isolation membrane after dissolving in the electrolyte, resulting in a decrease in the strength of the isolation membrane, thereby improving the fast charging performance and structural stability of the electrochemical device at low temperatures.

[0005] In a first aspect, the present application provides an isolation membrane, which includes a base membrane and a first coating disposed on at least one side of the base membrane, the first coating includes polydopamine and an adhesive polymer, and the Young's modulus of the base membrane is 52MPa~90MPa.

[0006] According to the present application, the Young's modulus of the base film in the isolation membrane is 52MPa~90MPa, and the first coating layer includes polydopamine. The polydopamine in the first coating layer can form a stable cross-linked structure with the binder polymer, which can promote the rapid transmission of lithium ions at low temperatures, thereby improving the fast charging performance of the electrochemical device at low temperatures. In addition, the satisfied Young's modulus of the base film can make the isolation membrane have a certain mechanical strength and structural stability, and it is not easy to swell after dissolving in the electrolyte, resulting in a decrease in the strength of the isolation membrane. The electrochemical device containing the isolation membrane has better low-temperature fast charging performance and structural stability. In addition, the coating can stabilize the positive electrode active material, reduce the dissolution of metal in the positive electrode active material, and capture the gas molecules produced by the interface side reactions, thereby improving the intermittent cycle performance of the electrochemical device at high temperature.

[0007] In some specific embodiments, the Young's modulus of the base film is 55 MPa-70 MPa.

[0008] In the above specific embodiment, the Young's modulus of the base film is 55MPa~70MPa, and the substrate has suitable elastic deformation ability, which can make the isolation membrane have good resistance to deformation under high and low temperature conditions. When in the fast charging test, it can resist the battery deformation caused by material expansion, so that the isolation membrane and the electrochemical device have stable structural performance and strength.

[0009] In some specific embodiments, the polydopamine in the first coating layer of the isolation membrane of the present application satisfies at least one of the following conditions: (1) the average molecular weight of the polydopamine is 120KDa~900KDa; (2) the melting point of the polydopamine is 160℃~220℃.

[0010] In the above specific embodiments, polydopamine satisfies any of the above items, and the polydopamine in the first coating can form a more stable cross-linked structure with the binder polymer, further improving the transmission speed of lithium ions at low temperatures, thereby further improving the fast charging performance of the electrochemical device at low temperatures.

[0011] In some embodiments, the first coating layer can further include inorganic ceramic particles, and / or the binder polymer includes dextrin.

[0012] In the above specific embodiment, the first coating may also include inorganic ceramic particles, and / or the binder polymer includes dextrin, and the first coating has better flexibility and stability, thereby improving the low-temperature fast charging performance and structural stability of the electrochemical device containing the isolation membrane.

[0013] In some specific embodiments, the adhesive polymer in the isolation film of the present application includes dextrin. Based on the total mass of the first coating, the mass percentage of polydopamine in the first coating is Awt%, and the mass percentage of dextrin in the first coating is Bwt%. The isolation film satisfies: 0.02≤A / B≤2.

[0014] In the above specific embodiment, the isolation membrane satisfies 0.02≤A / B≤2, and the formed polydopamine coating has higher structural stability, so that the isolation membrane has a certain strength, which can resist the structural deformation of the material caused by the expansion of other materials during fast charging, thereby improving the fast charging performance and structural stability of the electrochemical device at low temperatures and high temperature intermittent cycling performance.

[0015] In some specific embodiments, the isolation film of the present application may further include a second coating, the second coating is disposed on both sides of the base film, the first coating is disposed on at least one side outside the second coating, and the D90 of the particles in the second coating is 0.6 μm~10 μm.

[0016] In the above specific embodiment, the D90 of the particles in the second coating of the isolation membrane is 0.6μm~10μm, and the isolation membrane has a certain supporting strength and ability to resist deformation. It can also promote the migration of lithium ions, thereby improving the wetting ability of the electrolyte at high and low temperatures, reducing purple lithium precipitation at the interface, and improving the fast charging performance at low temperatures, structural stability and high temperature intermittent cycle performance.

[0017] In some specific embodiments, the D90 of the particles in the second coating is between 0.6 μm and 5 μm.

[0018] In the above specific embodiment, the D90 of the particles in the second coating layer of the isolation membrane of the present application is 0.6μm~5μm, and the isolation membrane has a more suitable supporting strength and ability to resist deformation. In addition, when the D90 range is in the preferred range, it can also further promote the migration of lithium ions, thereby improving the wetting ability of the electrolyte at high and low temperatures, reducing purple lithium precipitation at the interface, and optimizing the fast charging performance at low temperatures, structural stability and high temperature intermittent cycle performance.

[0019] In some specific embodiments, the isolation film of the present application may further include a second coating, the second coating is arranged on both sides of the base film, the first coating is arranged on at least one side outside the second coating, the thickness of the first coating is Cμm, the D90 of the particles in the second coating is Dμm, and the isolation film satisfies: 0.06≤C / D≤10.

[0020] In the above specific implementation, the separator satisfies 0.06≤C / D≤10, and the separator can better play its isolation and insulation role, effectively prevent direct contact between the positive and negative electrodes, and reduce the risk of short circuit. At the same time, improving the mechanical properties and thermal stability of the separator helps to improve the safety of the electrochemical device. In addition, it is conducive to the rapid transmission of lithium ions inside the battery, reducing the resistance to lithium ion diffusion, thereby improving the charge and discharge efficiency of the battery.

[0021] In some specific embodiments, the isolation film of the present application satisfies: 0.2≤C / D≤7.

[0022] In the above specific implementation, the isolation membrane satisfies 0.2≤C / D≤7, and the isolation membrane has better mechanical properties and thermal stability, thereby further improving the safety of the electrochemical device.

[0023] In some specific embodiments, the first coating layer of the isolation film of the present application satisfies at least one of the following: (1) the thickness of the first coating layer is 1 μm~4 μm; (2) the porosity of the first coating layer is 30%~65%; (3) the surface gloss of the base film is 1GU~5.5GU; (4) based on the total mass of the first coating layer, the mass percentage of polydopamine in the first coating layer is Awt%, the thickness of the first coating layer is Cμm, and the isolation film satisfies: 0.25≤A / C≤67.

[0024] In the above specific embodiment, the thickness of the first coating of the isolation membrane is 1μm~4μm, and the isolation membrane itself has suitable strength, thereby resisting the structural deformation of the material caused by the expansion of other materials during fast charging, thereby improving the fast charging performance and structural stability at low temperatures and high temperature intermittent cycle performance. When the thickness of the first coating is too thick, the energy density of the electrochemical device will be reduced, and the wettability of the electrolyte may be affected. When the thickness of the first coating is too thin, it cannot stabilize the positive electrode active material, and the isolation membrane cannot have a certain mechanical strength and structural stability. It is not easy to dissolve in the electrolyte and swell, resulting in a decrease in the strength of the isolation membrane. Therefore, the electrochemical device containing the isolation membrane cannot exert excellent low-temperature fast charging performance and structural stability.

[0025] The porosity of the first coating of the separator is 30%~65%, and the first coating maintains good structural stability during the battery's cyclic use. Extending the service life of the separator, thereby improving the overall cycle life of the battery. At the same time, it can provide sufficient and appropriate lithium ion transmission channels, allowing lithium ions to pass through the separator more smoothly during the charge and discharge process, improving the battery's charge and discharge efficiency, and thereby improving the battery's energy density and power density. If the porosity is too high, the first coating structure is not stable enough, which will cause confusion in the lithium ion transmission path, affecting the battery's charge and discharge efficiency and rate performance; if the porosity is too low, lithium ion transmission is blocked, the battery's charge and discharge speed will slow down, and the energy density will also be limited.

[0026] The surface glossiness of the base film of the separator is 1GU~5.5GU. The surface of the base film has a certain degree of flatness, so that the coating can better fit with the substrate, thereby improving the energy density of the electrochemical device. When the surface glossiness of the substrate is higher, the surface is smoother, but when the glossiness is too high, the surface interaction force between the coating and the substrate is less, and the difficulty of coating increases; when the glossiness is too low, the energy density of the electrochemical device is lower, and because the surface is too uneven, the safety risk of the electrochemical device is increased, and the pass rate of the side extrusion test of the electrochemical device is reduced.

[0027] The isolation membrane satisfies 0.25≤A / C≤67. The synergistic effect of the two can improve the mechanical strength of the isolation membrane, reduce the risk of rupture or damage of the isolation membrane in the complex environment inside the battery, enhance the protective effect of the isolation membrane on the internal structure of the battery, and improve the safety and service life of the battery. At the same time, it is beneficial to the transmission of lithium ions in the isolation membrane, reduce the internal resistance of the battery, and thus improve the charge and discharge efficiency of the battery.

[0028] In a second aspect, the present application provides an electrochemical device, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator according to the first aspect, wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet, and the electrolyte comprises a lithium salt and a non-aqueous solvent. The electrochemical device has better low-temperature fast charging performance and structural stability.

[0029] In some specific embodiments, the electrolyte of the electrochemical device of the present application satisfies at least one of the following: (1) the lithium salt includes at least one of lithium bis(trifluoromethylsulfonyl)imide and lithium difluorophosphate, and the mass percentage of lithium bis(trifluoromethylsulfonyl)imide or lithium difluorophosphate in the electrolyte is 0.01wt%~4.5wt% based on the total mass of the electrolyte; (2) the lithium salt includes lithium bis(trifluoromethylsulfonyl)imide and lithium difluorophosphate. At least one of the above, based on the total mass of the electrolyte, the mass percentage of lithium bis(trifluoromethylsulfonyl)imide, lithium difluorophosphate in the electrolyte is Fwt%, based on the total mass of the first coating, the mass percentage of polydopamine in the first coating is Awt%, and the electrochemical device satisfies: 6≤A / F≤3330; (3) the non-aqueous solvent includes propyl propionate, and based on the total mass of the electrolyte, the mass percentage of propyl propionate in the electrolyte is 20wt%~45wt%.

[0030] In the above specific embodiment, the electrolyte of the electrochemical device satisfies the mass percentage of lithium bis(trifluoromethylsulfonyl)imide, lithium difluorophosphate of 0.01wt%~4.5wt% and / or the mass percentage of propyl propionate of 20wt%~45wt%. Lithium bis(trifluoromethylsulfonyl)imide can promote the activation of propyl propionate, thereby further promoting the circulation of lithium ions in the electrolyte, improving the low-temperature fast charging performance of the electrochemical device and reducing the voltage drop at high temperature.

[0031] The electrochemical device satisfies 6≤A / F≤3330, and polydopamine and at least one of lithium bis(trifluoromethylsulfonyl)imide and lithium difluorophosphate work synergistically to make the interface inside the battery more stable, reduce the increase of interface resistance, and improve the long-term cycle performance of the battery. At the same time, polydopamine improves the interface compatibility between the isolation membrane and the electrolyte, and the stable solid electrolyte interface film (SEI film) formed by lithium bis(trifluoromethylsulfonyl)imide or lithium difluorophosphate helps to further stabilize the electrode / electrolyte interface. The two work together to make the interface inside the battery more stable, reduce the increase of interface resistance, and improve the long-term cycle performance of the battery.

[0032] In some specific embodiments, the electrolyte of the electrochemical device of the present application includes propyl propionate and lithium bis(fluorosulfonyl)imide; based on the total mass of the electrolyte, the mass percentage of propyl propionate in the electrolyte is Gwt%, the mass percentage of lithium bis(fluorosulfonyl)imide is Hwt%, and the electrochemical device satisfies: 0.02≤H / G≤0.48.

[0033] In the above specific embodiment, the electrochemical device satisfies 0.02≤H / G≤0.48, which can improve the viscosity of the electrolyte, thereby improving low-temperature fast charging and overcurrent safety, and at the same time, reducing the increase in the impedance value obtained by the high-temperature electrochemical impedance spectroscopy (EIS) test.

[0034] In some specific embodiments, the electrochemical device of the present application satisfies: 0.02≤H / G≤0.3.

[0035] In the above specific embodiment, the electrochemical device satisfies 0.02≤H / G≤0.3, which can further improve the viscosity of the electrolyte, thereby improving the low-temperature fast charging performance and overcurrent safety, and at the same time, further reducing the increase in the impedance value obtained by the high-temperature EIS test.

[0036] In some specific embodiments, the electrolyte of the electrochemical device of the present application may further include an additive, wherein the additive includes at least one of 1,3-propane sultone, vinyl ethylene carbonate, vinyl sulfate and 1,2,3-tris(2-cyano)propane.

[0037] In the above specific embodiment, 1,3-propane sultone, vinyl ethylene carbonate, vinyl sulfate and 1,2,3-tri(2-cyano)propane are used as battery electrolyte additives to isolate the electrode from the solvent to avoid electrode damage, while inhibiting electrolyte decomposition, reducing battery material loss, and effectively extending battery life; it can also reduce battery internal resistance, optimize charge and discharge performance, and improve battery rate performance and low-temperature charge and discharge performance; in addition, in a high temperature environment, it can reduce gas generation and battery expansion, reduce self-discharge rate, improve high-temperature cycle and storage performance of the battery, and significantly enhance battery safety.

[0038] In some specific embodiments, the electrochemical device of the present application satisfies at least one of the following conditions: (1) the additive includes 1,3-propane sultone, and the mass percentage of 1,3-propane sultone in the electrolyte is 0.2wt%~3.5wt% based on the total mass of the electrolyte; (2) the additive includes vinyl ethylene carbonate, and the mass percentage of vinyl ethylene carbonate in the electrolyte is 0.1wt%~3.5wt% based on the total mass of the electrolyte; (3) the additive includes vinyl sulfate, and the mass percentage of vinyl sulfate in the electrolyte is 0.1wt%~3.5wt%; (4) the additive includes 1,2,3-tris(2-cyanato)propane. Based on the total mass of the electrolyte, the mass percentage of 1,2,3-tris(2-cyanato)propane in the electrolyte is 0.1wt%~2.8wt%; (5) the additive includes 1,3-propane sultone. Based on the total mass of the electrolyte, the mass percentage of 1,3-propane sultone is Iwt%. Based on the total mass of the first coating, the mass percentage of polydopamine in the first coating is Awt%. The electrochemical device satisfies: 8≤A / I≤334.

[0039] In the above specific embodiment, the electrolyte of the electrochemical device contains 1,3-propane sultone and the mass percentage of 1,3-propane sultone in the electrolyte is 0.2wt%~3.5wt%. 1,3-propane sultone can form a stable SEI film on the surface of the positive electrode material, thereby improving the low-temperature fast charging performance and overcurrent safety of the electrochemical device.

[0040] The electrolyte of the electrochemical device contains vinyl ethylene carbonate and the mass percentage of vinyl ethylene carbonate in the electrolyte is 0.1wt%~3.5wt%. Vinyl ethylene carbonate can form a uniform and dense SEI film on the surface of the negative electrode material, thereby improving the low-temperature fast charging performance and overcurrent safety of the electrochemical device.

[0041] The electrolyte of the electrochemical device contains vinyl sulfate and the mass percentage of vinyl sulfate in the electrolyte is 0.1wt%~3.5wt%. Vinyl sulfate can form a denser SEI film on the surface of the negative electrode material and capture gas molecules generated by side reactions at the interface between the negative electrode and the electrolyte, thereby improving the low-temperature fast charging performance and overcurrent safety of the electrochemical device.

[0042] The electrolyte of the electrochemical device contains 1,2,3-tris(2-cyanato)propane and the mass percentage of 1,2,3-tris(2-cyanato)propane in the electrolyte is 0.1wt%~2.8wt%. 1,2,3-tris(2-cyanato)propane can improve the viscosity of the electrolyte and is conducive to forming a stable cathode electrolyte interface film (Cathode Electrolyte Interface, referred to as interface CEI film), thereby improving low-temperature fast charging, overcurrent safety and reducing the increase in impedance value obtained by high-temperature EIS test.

[0043] The electrochemical device meets 8≤A / I≤334. Polydopamine and 1,3-propane sultone synergistically enhance the bonding force between the components inside the battery, making the battery structure more stable, able to withstand volume changes and mechanical stress during charging and discharging, and reducing interface separation and structural damage. It can also optimize the transmission path of lithium ions between the separator and the electrolyte, making lithium ion transmission more efficient, reducing the ion migration resistance during the battery charging and discharging process, and improving the battery's charging and discharging efficiency and power performance.

[0044] In some specific embodiments, the electrochemical device satisfies at least one of the following: (1) the additive includes 1,3-propane sultone, and the mass percentage of 1,3-propane sultone in the electrolyte is 0.2 wt%~2 wt% based on the total mass of the electrolyte; (2) the additive includes vinyl ethylene carbonate, and the mass percentage of vinyl ethylene carbonate in the electrolyte is 0.1 wt%~1.8 wt% based on the total mass of the electrolyte; (3) the additive includes vinyl sulfate, and the mass percentage of vinyl sulfate in the electrolyte is 0.1 wt%~2.5 wt% based on the total mass of the electrolyte.

[0045] In the above specific embodiment, the electrolyte of the electrochemical device contains 1,3-propane sultone and the mass percentage of 1,3-propane sultone in the electrolyte is 0.2wt%~2wt%. 1,3-propane sultone can form a more stable SEI film on the surface of the positive electrode material, further improving the low-temperature fast charging performance and overcurrent safety of the electrochemical device.

[0046] The electrolyte of the electrochemical device contains vinyl ethylene carbonate and the mass percentage of vinyl ethylene carbonate in the electrolyte is 0.1wt%~1.8wt%. Vinyl ethylene carbonate can form a more uniform and dense SEI film on the surface of the negative electrode material, further improving the low-temperature fast charging performance and overcurrent safety of the electrochemical device.

[0047] The electrolyte of the electrochemical device contains vinyl sulfate and the mass percentage of vinyl sulfate in the electrolyte is 0.1wt%~2.5wt%. Vinyl sulfate can form a denser SEI film on the surface of the negative electrode material and capture gas molecules generated by side reactions at the interface between the negative electrode and the electrolyte, thereby improving the low-temperature fast charging performance and overcurrent safety of the electrochemical device.

[0048] In some specific embodiments, the electrode bonding strength between the separator and the negative electrode plate of the electrochemical device is 1.8 gf / 15 mm≤T≤3.6 gf / 15 mm.

[0049] In the above specific embodiment, the electrochemical device satisfies the electrode bonding strength between the isolation membrane and the negative electrode plate of 1.8gf / 15mm≤T≤3.6gf / 15mm, so that the isolation membrane and the negative electrode plate are not easily separated during the side extrusion test of the electrochemical device, so that the electrochemical device has certain structural strength and high-temperature cycle stability.

[0050] In some specific embodiments, the electrode bonding strength between the separator and the negative electrode plate is T gf / 15 mm, and the electrochemical device satisfies: 15≤X / T≤43.

[0051] In the above specific embodiment, the electrochemical device satisfies 15≤X / T≤43, and the separator has a certain flexibility to adapt to the volume change of the electrode, and can maintain a good bonding effect with the negative electrode plate, prevent the separator from separating from the plate, and maintain the stability of the internal structure of the battery. At the same time, the stable bonding state between the separator and the negative electrode plate helps to maintain the stability of the ion transmission channel. During the charge and discharge process, lithium ions can pass through the interface between the separator and the negative electrode plate more smoothly, reducing the obstacles to ion transmission and reducing the internal resistance of the battery, thereby improving the charge and discharge efficiency and power performance of the battery.

[0052] In a third aspect, the present application provides an electronic device, comprising the electrochemical device described above in the present application. DETAILED DESCRIPTION

[0053] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0054] As used in this application, the terms "including," "containing," and "comprising" are used in their open, non-limiting sense.

[0055] In addition, sometimes amounts, ratios and other numerical values ​​are presented in range format herein. It should be understood that such range format is for convenience and brevity, and should be flexibly understood to include not only the numerical values ​​explicitly specified as range limits, but also all individual numerical values ​​or sub-ranges encompassed within the range, as if each numerical value and sub-range were explicitly specified.

[0056] In the detailed description and claims, a list of items connected by the terms "one or more of," "one or more of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A or B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, or C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0057] In the structure of secondary batteries, the separator plays an indispensable role. On the one hand, it blocks the direct contact between the positive and negative electrodes to avoid the risk of short circuit; on the other hand, it allows ions to pass through to maintain the electrochemical reaction inside the battery.

[0058] With the advancement of technology, the application scenarios of secondary batteries are constantly expanding, covering areas such as daily electronic devices, electric vehicles, and energy storage power stations. Different application scenarios have put forward strict requirements on the performance of secondary batteries. In low temperature environments, such as the start-up and endurance of electric vehicles in cold winter, and the stable operation of outdoor electronic equipment, higher requirements are placed on the fast charging performance and stability of secondary batteries. However, under low temperature conditions, lithium dendrites are prone to form at the negative electrode of secondary batteries. The presence of lithium dendrites will not only reduce the charging and discharging efficiency of the battery, but may also penetrate the isolation membrane and cause a short circuit in the battery, thereby affecting the safety and service life of the battery.

[0059] At the same time, under extreme conditions such as high temperature, such as the continuous operation of energy storage power stations in hot summer, secondary batteries need to have good mechanical properties to ensure stable operation. The mechanical strength, thermal stability and other characteristics of the separator play a key role in the performance of secondary batteries under these extreme conditions. Therefore, the development of high-performance separators that can meet the performance requirements of secondary batteries under various complex working conditions has become an important issue that needs to be solved in the current battery field.

[0060] Based on the above problems, the present application provides an isolation membrane, an electrochemical device and an electronic device. The isolation membrane has good structural stability and high mechanical strength, which can effectively reduce the problem of swelling of the isolation membrane after dissolving in the electrolyte, resulting in reduced strength of the isolation membrane, thereby improving the fast charging performance and structural stability of the electrochemical device at low temperatures.

[0061] The following is a detailed description of the implementation of the present application.

[0062] Isolation film In a first aspect, an embodiment of the present application provides an isolation membrane, which includes a base membrane and a first coating disposed on at least one side of the base membrane, the first coating includes polydopamine and an adhesive polymer, and the Young's modulus of the base membrane is X MPa, 52≤X≤90.

[0063] For example, X may be 52, 55, 58, 60, 62, 65, 68, 70, 72, 75, 78, 80, 82, 85, 88, 90, or a range consisting of any of the above values.

[0064] Optional, 55≤X≤90, 55≤X≤88, 55≤X≤86, 55≤X≤84, 55≤X≤82, 55≤X≤80, 55≤X≤78, 55≤X≤76, 55≤X≤74, 55≤X≤72, 55≤X≤70.

[0065] According to the present application, when the Young's modulus of the base film in the isolation membrane satisfies 52≤X≤90, and the first coating layer includes polydopamine and a binder polymer, the polydopamine in the first coating layer can form a stable cross-linked structure with the binder polymer, which can promote the rapid transmission of lithium ions at low temperatures, thereby improving the fast charging performance of the electrochemical device at low temperatures. In addition, the satisfied Young's modulus of the base film can make the isolation membrane have a certain mechanical strength and structural stability, and it is not easy to swell after dissolving in the electrolyte, resulting in a decrease in the strength of the isolation membrane. The electrochemical device containing the isolation membrane has better low-temperature fast charging performance and structural stability. In addition, the coating can stabilize the positive electrode active material, reduce the dissolution of metal in the positive electrode active material, and capture the gas molecules produced by the interface side reactions, thereby improving the intermittent cycle performance of the electrochemical device at high temperatures.

[0066] It should be noted that the Young's modulus of the base film and the polydopamine in the first coating can be detected using methods and instruments known in the art. For example, the isolation membrane can be obtained by disassembling the electrochemical device and then further disassembling the base film. The method specified in JIS K7127 is used to set a suitable stretching speed according to the material properties and standard requirements, and start the stretching tester to apply a stretching force to the sample. During the stretching process, the tester automatically records the tension at different times and the corresponding elongation of the sample, calculates the stress and strain, and then obtains the Young's modulus of the base film; the first coating can be dissolved in a suitable solvent, and a gas chromatography-mass spectrometer (GC-MS) can be used to detect the specific soluble components in the first coating and the mass percentage of each component.

[0067] In some embodiments, in some specific embodiments, the polydopamine in the first coating layer of the isolation membrane of the present application satisfies at least one of the following conditions: (1) the average molecular weight of the polydopamine is 120KDa~900KDa, for example, it can be 120KDa, 150KDa, 180KDa, 200KDa, 250KDa, 300KDa, 350KDa, 400KDa, 450KDa, 500KDa, 550KDa, 600KDa, 650KDa, 700KDa, 750KDa, 800KDa, 850KDa, 900KDa, or a range consisting of any of the above values; (2) the melting point of the polydopamine is 160℃~220℃, for example, it can be 160℃, 170℃, 180℃, 190℃, 200℃, 210℃, 220℃, or a range consisting of any of the above values.

[0068] It should be noted that the average molecular weight and melting point of polydopamine can be detected using methods and instruments known in the art. For example, the isolation membrane can be obtained by disassembling the electrochemical device and then further disassembling and separating polydopamine. The solution can be injected into the GPC instrument by gel permeation chromatography (GPC), and a suitable chromatographic column and mobile phase are selected. By comparing with the standard curve, the average molecular weight of polydopamine can be obtained; differential scanning calorimetry (DSC) can be used to put an appropriate amount of polydopamine sample into the sample cell of the DSC, and the same mass of reference material (such as aluminum oxide, etc.) can be placed in the reference cell. Then the sample cell and the reference cell are placed in the DSC instrument, and the temperature is increased at a certain heating rate (such as 5°C / min, 10°C / min, etc.). The instrument will record the change in heat flow rate between the sample and the reference material during the entire heating process. By analyzing the obtained DSC curve, the position and temperature of the endothermic peak are determined to determine the melting point of polydopamine.

[0069] According to this embodiment, polydopamine satisfies any of the above items, and the polydopamine in the first coating can form a more stable cross-linked structure with the binder polymer, further improving the transmission speed of lithium ions at low temperatures, thereby further improving the fast charging performance of the electrochemical device at low temperatures.

[0070] In some embodiments, the first coating layer may also contain inorganic ceramic particles, and / or the binder polymer may include dextrin. The first coating layer may include dextrin and / or inorganic ceramic particles, and the first coating layer may have better flexibility and stability, thereby improving the low-temperature fast charging performance and structural stability of the electrochemical device including the isolation membrane.

[0071] In some embodiments, the adhesive polymer in the isolation film of the present application includes dextrin. Based on the total mass of the first coating, the mass percentage of polydopamine in the first coating is Awt%, and the mass percentage of dextrin in the first coating is Bwt%. The isolation film satisfies: 0.02≤A / B≤2.

[0072] For example, A / B may be 0.02, 0.05, 0.08, 0.1, 0.2, 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, or a range consisting of any of the above values.

[0073] According to this embodiment, the isolation membrane satisfies 0.02≤A / B≤2, and the formed polydopamine coating has higher structural stability, so that the isolation membrane has a certain strength, which can resist the structural deformation of the material caused by the expansion of other materials during fast charging, thereby improving the fast charging performance and structural stability of the electrochemical device at low temperatures and high temperature intermittent cycling performance.

[0074] In some embodiments, the isolation film of the present application may further include a second coating layer, the second coating layer is disposed on both sides of the base film, the first coating layer is disposed on at least one side outside the second coating layer, and the D90 of the particles in the second coating layer is D μm, 0.6 ≤ D ≤ 10. For example, D may be 0.6, 0.8, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, or a range consisting of any of the above values.

[0075] Optional, 0.6≤D≤9.5, 0.6≤D≤9, 0.6≤D≤8.5, 0.6≤D≤8, 0.6≤D≤7.5, 0.6≤D≤7, 0.6≤D≤6.5, 0.6≤D≤6.

[0076] According to this embodiment, the particles in the second coating layer of the isolation membrane satisfy 0.6≤D≤10, and the isolation membrane has a certain supporting strength and ability to resist deformation. At the same time, it can also promote the migration of lithium ions, thereby improving the wetting ability of the electrolyte at high and low temperatures, reducing purple lithium precipitation at the interface, and improving the fast charging performance at low temperatures, structural stability and high temperature intermittent cycle performance.

[0077] In some embodiments, the isolation film of the present application may further include a second coating layer, the second coating layer is disposed on both sides of the base film, the first coating layer is disposed on at least one side outside the second coating layer, the thickness of the first coating layer is C μm, the D90 of the particles in the second coating layer is D μm, and the isolation film satisfies: 0.06≤C / D≤10. For example, C / D may be 0.06, 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, or a range consisting of any of the above values.

[0078] Optional, 0.1≤C / D≤10, 0.2≤C / D≤10, 0.2≤C / D≤9.5, 0.2≤C / D≤9, 0.2≤C / D≤8.5, 0.2≤C / D≤8, 0.2≤C / D≤7.5, 0.2≤C / D≤7.

[0079] According to this embodiment, the separator satisfies 0.06≤C / D≤10, and the separator can better play its isolation and insulation role, effectively prevent direct contact between the positive and negative electrodes, and reduce the risk of short circuit. At the same time, improving the mechanical properties and thermal stability of the separator helps to improve the safety of the electrochemical device. In addition, it is conducive to the rapid transmission of lithium ions inside the battery, reducing the resistance to lithium ion diffusion, thereby improving the charge and discharge efficiency of the battery.

[0080] In some embodiments, the first coating layer of the isolation film of the present application satisfies at least one of the following: (1) the thickness of the first coating layer is C μm, 1≤C≤4, for example, it can be 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, or a range consisting of any of the above values; (2) the porosity of the first coating layer is 30% to 65%, for example, it can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, or a range consisting of any of the above values; (3) the surface gloss of the base film is E GU, 1≤E≤5.5, for example, E can be 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.8, 5, 5.2, 5.5, or any range thereof; (4) based on the total mass of the first coating, the mass percentage of polydopamine in the first coating is Awt%, the thickness of the first coating is Cμm, and the isolation film satisfies: 0.25≤A / C≤67, for example, A / C can be 0.25, 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 67, or any range thereof.

[0081] According to this embodiment, the first coating of the isolation membrane satisfies 1≤C≤4, and the isolation membrane itself has suitable strength, thereby resisting the structural deformation of the material caused by the expansion of other materials during fast charging, thereby improving the fast charging performance and structural stability at low temperatures and high-temperature intermittent cycle performance. When the thickness of the first coating is too thick, the energy density of the electrochemical device will be reduced, and the wettability of the electrolyte may be affected. When the thickness of the first coating is too thin, it cannot play the role of stabilizing the positive electrode active material, nor can it make the isolation membrane have a certain mechanical strength and structural stability. It is not easy to dissolve in the electrolyte and swell, resulting in a decrease in the strength of the isolation membrane. Therefore, the electrochemical device containing the isolation membrane cannot exert excellent low-temperature fast charging performance and structural stability.

[0082] The porosity of the first coating of the separator is 30%~65%, and the first coating maintains good structural stability during the battery's cyclic use. Extending the service life of the separator, thereby improving the overall cycle life of the battery. At the same time, it can provide sufficient and appropriate lithium ion transmission channels, allowing lithium ions to pass through the separator more smoothly during the charge and discharge process, improving the battery's charge and discharge efficiency, and thereby improving the battery's energy density and power density. If the porosity is too high, the first coating structure is not stable enough, which will cause confusion in the lithium ion transmission path, affecting the battery's charge and discharge efficiency and rate performance; if the porosity is too low, lithium ion transmission is blocked, the battery's charge and discharge speed will slow down, and the energy density will also be limited.

[0083] The base film of the separator meets 1≤E≤5.5, and the surface of the base film has a certain degree of flatness, so that the coating can be better embedded with the substrate, thereby improving the energy density of the electrochemical device. When the glossiness of the substrate surface is higher, the surface is smoother, but when the glossiness is too high, the surface interaction between the coating and the substrate will be less, and the difficulty of coating will increase; when the glossiness is too low, the energy density of the electrochemical device will be lower, and because the surface is too uneven, the safety risk of the electrochemical device is increased, and the pass rate of the side extrusion test of the electrochemical device is reduced.

[0084] The isolation membrane satisfies 0.25≤A / C≤67. The synergistic effect of the two can improve the mechanical strength of the isolation membrane, reduce the risk of rupture or damage of the isolation membrane in the complex environment inside the battery, enhance the protective effect of the isolation membrane on the internal structure of the battery, and improve the safety and service life of the battery. At the same time, it is beneficial to the transmission of lithium ions in the isolation membrane, reduce the internal resistance of the battery, and thus improve the charge and discharge efficiency of the battery.

[0085] It should be noted that the thickness C of the first coating layer can be detected using methods and instruments known in the art. For example, the isolation membrane can be obtained by disassembling the electrochemical device, and the isolation membrane can be sliced ​​using a scanning electron microscope (SEM) measurement method to prepare a flat cross-sectional sample. The sample is placed in a SEM device, and a suitable acceleration voltage and scanning parameters are selected to obtain a high-resolution cross-sectional image. The thickness of the first coating layer is directly measured on the image using the image processing software provided by the SEM.

[0086] The surface glossiness of the base film can be detected by methods and instruments known in the art. For example, the electrochemical device can be disassembled to obtain a separator, the separator can be disassembled to obtain the base film, and then the surface glossiness can be measured at a reflection angle of 60° using "micro-TRI-gloss-s" manufactured by BYK.

[0087] The porosity of the first coating can be detected by methods and instruments known in the art. For example, the isolation membrane can be obtained by disassembling the electrochemical device, and the first coating can be obtained after disassembling the isolation membrane, and then the gas adsorption method is used to perform vacuum degassing at a certain temperature to remove impurities and gases adsorbed on the surface. Then the sample is placed in the sample tube of the gas adsorption instrument, the instrument is cooled to about liquid nitrogen temperature (77K), nitrogen at different pressures is introduced, and the adsorption amount of nitrogen is measured. By analyzing the adsorption isotherm, the specific surface area of ​​the sample is calculated using methods such as the BET equation, and then the porosity is calculated in combination with relevant models. Alternatively, the first coating is appropriately treated by scanning electron microscopy (SEM) combined with image analysis, such as coating, to increase the conductivity and imaging quality of the sample. Then the sample is placed in a scanning electron microscope, and the appropriate magnification and imaging parameters are selected to obtain a SEM image of the coating. Import the SEM image into the image analysis software, and distinguish the pores from the coating matrix through threshold setting, binarization processing and other operations. The software will automatically calculate parameters such as the area and number of pores, and then derive the porosity.

[0088] Electrochemical Devices In a second aspect, the present application provides an electrochemical device, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator according to the first aspect, wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet, and the electrolyte comprises a lithium salt and a non-aqueous solvent. The electrochemical device has better low-temperature fast charging performance and structural stability.

[0089] In some specific embodiments, the electrolyte of the electrochemical device of the present application satisfies at least one of the following: (1) the lithium salt includes at least one of lithium bis(trifluoromethylsulfonyl)imide and lithium difluorophosphate, and the mass percentage of lithium bis(trifluoromethylsulfonyl)imide or lithium difluorophosphate in the electrolyte is Fwt%, based on the total mass of the electrolyte, 0.01≤F≤4.5, for example, F can be 0.01, 0.05, 0.1, 0.5, 1, 1.5, 2, 1.5, 2.5, 3, 3.5, 4, 4.5, or a range consisting of any of the above values; (2) the lithium salt includes at least one of lithium bis(trifluoromethylsulfonyl)imide and lithium difluorophosphate, and the mass percentage of lithium bis(trifluoromethylsulfonyl)imide or lithium difluorophosphate in the electrolyte is Fwt%, based on the total mass of the electrolyte, 0.01≤F≤4.5, for example, F can be 0.01, 0.05, 0.1, 0.5, 1, 1.5, 2, 1.5, 2.5, 3, 3.5, 4, 4.5, or a range consisting of any of the above values; The mass percentage of lithium fluorophosphate is Fwt%, based on the total mass of the first coating, the mass percentage of polydopamine in the first coating is Awt%, and the electrochemical device satisfies: 6≤A / F≤3330, for example, A / F can be 6, 50, 100, 300, 500, 700, 1000, 1200, 1500, 1800, 2000, 2200, 2500, 2800, 3000, 3200, 3330, or a range consisting of any of the above values; (3) the non-aqueous solvent includes propyl propionate, and based on the total mass of the electrolyte, the mass percentage of propyl propionate in the electrolyte is Gwt%, 20≤G≤45, for example, G can be 20, 22, 25, 28, 30, 32, 35, 38, 40, 42, 45, or a range consisting of any of the above values.

[0090] According to this embodiment, the electrolyte of the electrochemical device satisfies 0.01≤F≤4.5 and / or 20≤G≤45, and lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonyl)imide or lithium difluorophosphate can promote the activation of propyl propionate, thereby further promoting the circulation of lithium ions in the electrolyte, improving the low-temperature fast charging performance of the electrochemical device and reducing the voltage drop at high temperature.

[0091] The electrochemical device satisfies 6≤A / F≤3330, and polydopamine and at least one of lithium bis(trifluoromethylsulfonyl)imide and lithium difluorophosphate work synergistically to make the interface inside the battery more stable, reduce the increase of interface resistance, and improve the long-term cycle performance of the battery. At the same time, polydopamine improves the interface compatibility between the isolation membrane and the electrolyte, and the stable solid electrolyte interface film (SEI film) formed by lithium bis(trifluoromethylsulfonyl)imide or lithium difluorophosphate helps to further stabilize the electrode / electrolyte interface. The two work together to make the interface inside the battery more stable, reduce the increase of interface resistance, and improve the long-term cycle performance of the battery.

[0092] It should be noted that the mass percentage of lithium difluorooxalate borate in the electrolyte can be detected using methods or instruments known in the art. For example, the electrochemical device can be disassembled and centrifuged to obtain the electrolyte, and then tested by ion chromatography (IC). The retention time can be used to qualitatively identify some components (such as lithium salts) in the electrolyte, and the corresponding mass percentage can be calculated by peak area; the mass percentage of some components (such as organic solvents) in the electrolyte can be detected by gas chromatography-mass spectrometry (GC-MS).

[0093] In some embodiments, the electrolyte of the electrochemical device of the present application includes propyl propionate and lithium bis(fluorosulfonyl)imide; based on the total mass of the electrolyte, the mass percentage of propyl propionate in the electrolyte is Gwt%, the mass percentage of lithium bis(fluorosulfonyl)imide is Hwt%, and the electrochemical device satisfies: 0.02≤H / G≤0.48. For example, H / G can be 0.02, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, 0.22, 0.25, 0.28, 0.3, 0.32, 0.35, 0.38, 0.4, 0.42, 0.45, 0.48, or a range consisting of any of the above values.

[0094] Optionally, 0.02≤H / G≤0.46, 0.02≤H / G≤0.44, 0.02≤H / G≤0.42, 0.02≤H / G≤0.4, 0.02≤H / G≤0.38, 0.02≤H / G≤0.36, 0.02≤H / G≤0.34, 0.02≤H / G≤0.32, 0.02≤H / G≤0.3.

[0095] According to this embodiment, the electrochemical device satisfies 0.02≤H / G≤0.48, which can improve the viscosity of the electrolyte, thereby improving low-temperature fast charging and overcurrent safety, and at the same time, reducing the increase in the impedance value obtained by the high-temperature EIS test.

[0096] In some embodiments, the electrolyte of the electrochemical device of the present application may further include an additive, wherein the additive includes at least one of 1,3-propane sultone, vinyl ethylene carbonate, vinyl sulfate, and 1,2,3-tris(2-cyano)propane.

[0097] According to this embodiment, 1,3-propane sultone, vinyl ethylene carbonate, vinyl sulfate and 1,2,3-tri(2-cyano)propane are used as battery electrolyte additives to isolate the electrode from the solvent to avoid electrode damage, while inhibiting electrolyte decomposition, reducing battery material loss, and effectively extending battery life; it can also reduce battery internal resistance, optimize charge and discharge performance, and improve battery rate performance and low-temperature charge and discharge performance; in addition, in a high temperature environment, it can reduce gas generation and battery expansion, reduce self-discharge rate, improve high-temperature cycle and storage performance of the battery, and significantly enhance battery safety.

[0098] In some specific embodiments, the electrochemical device of the present application satisfies at least one of the following: (1) the additive includes 1,3-propane sultone, and the mass percentage of 1,3-propane sultone in the electrolyte is 1wt%, based on the total mass of the electrolyte, 0.2≤I≤3.5, for example, I can be 0.2, 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, or a range consisting of any of the above values; (2) the additive includes vinyl ethylene carbonate, based on the total mass of the electrolyte. The weight percentage of vinyl ethylene carbonate in the electrolyte is Jwt%, and 0.1≤J≤3.5. For example, J can be 0.1, 0.2, 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, or any range thereof; (3) the additive includes vinyl sulfate. Based on the total weight of the electrolyte, the weight percentage of vinyl sulfate in the electrolyte is Kwt%, and 0.1≤K≤3.5. For example, K can be 0.1, 0.2, 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, or any range thereof; .8, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, or any range thereof; (4) the additive includes 1,2,3-tris(2-cyanato)propane, and the mass percentage of 1,2,3-tris(2-cyanato)propane in the electrolyte is Lwt%, based on the total mass of the electrolyte, and 0.1≤L≤2.8. For example, L can be 0.1, 0.2, 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, or any range thereof. (5) the additive includes 1,3-propane sultone, the mass percentage of 1,3-propane sultone based on the total mass of the electrolyte is 1wt%, the mass percentage of polydopamine in the first coating is Awt%, and the electrochemical device satisfies: 8≤A / I≤334, for example, A / F can be 8, 20, 50, 80, 100, 120, 150, 180, 200, 220, 250, 280, 300, 320, 334, or a range consisting of any of the above values.

[0099] Optional, 0.2≤I≤3.2, 0.2≤I≤3, 0.2≤I≤2.8, 0.2≤I≤2.6, 0.2≤I≤2.4, 0.2≤I≤2.2, 0.2≤I≤2.

[0100] Optional, 0.1≤J≤3.4, 0.1≤J≤3.2, 0.1≤J≤3, 0.1≤J≤2.8, 0.1≤J≤2.6, 0.1≤J≤2.4, 0.1≤J≤2.2, 0.1≤J≤2, 0.1≤J≤1.8.

[0101] Optionally, 0.1≤K≤3.4, 0.1≤K≤3.3, 0.1≤K≤3.2, 0.1≤K≤3.1, 0.1≤K≤3, 0.1≤K≤2.9, 0.1≤K≤2.8, 0.1≤K≤2.7, 0.1≤K≤2.6, 0.1≤K≤2.5.

[0102] In this embodiment, the electrolyte of the electrochemical device contains 1,3-propane sultone and satisfies 0.2≤I≤3.5. 1,3-propane sultone can form a stable SEI film on the surface of the positive electrode material, thereby improving the low-temperature fast charging performance and overcurrent safety of the electrochemical device.

[0103] The electrolyte of the electrochemical device contains vinyl ethylene carbonate and satisfies 0.1≤J≤3.5. Vinyl ethylene carbonate can form a uniform and dense SEI film on the surface of the negative electrode material, thereby improving the low-temperature fast charging performance and overcurrent safety of the electrochemical device.

[0104] The electrolyte of the electrochemical device contains vinyl sulfate and satisfies 0.1≤K≤3.5. Vinyl sulfate can form a denser SEI film on the surface of the negative electrode material and capture gas molecules generated by side reactions at the interface between the negative electrode and the electrolyte, thereby improving the low-temperature fast charging performance and overcurrent safety of the electrochemical device.

[0105] The electrolyte of the electrochemical device contains 1,2,3-tri(2-cyanato)propane and satisfies 0.1≤L≤2.8. 1,2,3-tri(2-cyanato)propane can improve the viscosity of the electrolyte and is conducive to forming a stable interfacial CEI film, thereby improving low-temperature fast charging, overcurrent safety and reducing the increase in impedance value obtained by high-temperature EIS testing.

[0106] The electrochemical device meets 8≤A / I≤334. Polydopamine and 1,3-propane sultone synergistically enhance the bonding force between the components inside the battery, making the battery structure more stable, able to withstand volume changes and mechanical stress during charging and discharging, and reducing interface separation and structural damage. It can also optimize the transmission path of lithium ions between the separator and the electrolyte, making lithium ion transmission more efficient, reducing the ion migration resistance during the battery charging and discharging process, and improving the battery's charging and discharging efficiency and power performance.

[0107] In some embodiments, the electrode bonding strength between the separator and the negative electrode of the electrochemical device is Tgf / 15mm, 1.8≤T≤3.6. For example, T can be 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, or a range consisting of any of the above values.

[0108] According to this embodiment, the electrochemical device satisfies 1.8≤T≤3.6, so that the separator and the negative electrode plate are not easily separated during the side compression test of the electrochemical device, so that the electrochemical device has a certain structural strength and high-temperature cycle stability. In addition, when the electrochemical device is subjected to a heat test, the corner area of ​​the electrochemical device tends to separate, thereby improving the structural stability of the electrochemical device.

[0109] It should be noted that the electrode bonding strength of the separator and the negative electrode plate can be tested using methods and equipment known in the art. For example, one end of the sample is fixed to the upper fixture of the testing machine, the separator at the other end is separated from the negative electrode plate, and the separator is fixed to the lower fixture. Set the tensile speed of the testing machine and start the testing machine to perform a peeling test. The testing machine automatically records the force-displacement curve during the peeling process, takes the average force value of the stable section in the curve as the peeling force, and calculates the bonding strength according to the formula. For another example, the diaphragm is laminated on a carbon sheet with a thickness of 200 μm so that the adhesive layer of the diaphragm faces the carbon sheet, and is measured by compressing and bonding the diaphragm at 80°C, using a hot press at 20 MPa for 30 seconds, and peeling the diaphragm at 180° using UTM equipment according to ASTM D903 to obtain the bonding strength.

[0110] In some embodiments, the electrode bonding strength between the separator and the negative electrode plate is T gf / 15 mm, and the electrochemical device satisfies: 15≤X / T≤43. For example, X / T can be 15, 18, 20, 22, 25, 28, 30, 32, 35, 38, 40, 43, or a range consisting of any of the above values.

[0111] In this embodiment, the electrochemical device satisfies 15≤X / T≤43, and the separator has a certain flexibility to adapt to the volume change of the electrode, and can maintain a good bonding effect with the negative electrode plate, prevent the separator from separating from the plate, and maintain the stability of the internal structure of the battery. At the same time, the stable bonding state between the separator and the negative electrode plate helps to maintain the stability of the ion transmission channel. During the charge and discharge process, lithium ions can pass through the interface between the separator and the negative electrode plate more smoothly, reducing the obstacles to ion transmission and reducing the internal resistance of the battery, thereby improving the battery's charge and discharge efficiency and power performance.

[0112] In some embodiments, the electrochemical device further comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet and the negative electrode sheet are separated by a separator disposed therebetween. In some embodiments, the positive electrode sheet comprises a positive current collector and a positive electrode active material layer disposed on the positive current collector, the positive electrode active material layer may include a positive electrode active material, the negative electrode sheet comprises a negative current collector and a negative electrode active material layer disposed on the negative current collector, the negative electrode active material layer may include a negative electrode active material.

[0113] In some embodiments, the negative electrode plate may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer may be disposed on one or both sides of the negative electrode current collector. In some embodiments, the negative electrode current collector may be at least one of a copper foil, a nickel foil, or a carbon-based current collector. In some embodiments, the thickness of the negative electrode current collector may be 1 μm to 200 μm. In some embodiments, the negative electrode active material layer may be coated only on a partial area of ​​the negative electrode current collector. In some embodiments, the thickness of the negative electrode active material layer may be 10 μm to 500 μm. It should be understood that these are exemplary only and other suitable thicknesses may be used.

[0114] In some embodiments, as described above, the negative electrode active material layer includes a negative electrode active material. In some embodiments, the negative electrode active material includes at least one of natural graphite, artificial graphite, or a silicon-based material. In some embodiments, the silicon-based material includes at least one of silicon, a silicon-oxygen compound, a silicon-carbon compound, or a silicon alloy.

[0115] In some embodiments, the negative electrode active material layer may also include a negative electrode conductor and / or a negative electrode binder. The negative electrode conductor may include at least one of carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes, or carbon fibers. In some embodiments, the negative electrode binder may include at least one of carboxymethyl cellulose (CMC), polyacrylic acid, polyacrylic acid salt, polyacrylate, polyvinyl pyrrolidone, polyimide, polysiloxane, or styrene-butadiene rubber. It should be understood that the materials disclosed above are only exemplary, and the negative electrode active material layer may be any other suitable material. In some embodiments, the mass ratio of the negative electrode active material, the negative electrode conductor, and the negative electrode binder in the negative electrode active material layer may be (80~99): (0.5~10): (0.5~10), and it should be understood that this is only exemplary and not intended to limit the present application.

[0116] In some embodiments, the positive electrode plate includes a positive current collector and a positive active material layer disposed on the positive current collector. The positive active material layer may be located on one or both sides of the positive current collector. In some embodiments, the positive current collector may be made of aluminum foil, and of course, other positive current collectors commonly used in the art may also be used. In some embodiments, the thickness of the positive current collector may be 1 μm to 200 μm. In some embodiments, the positive active material layer may be coated only on a partial area of ​​the positive current collector. In some embodiments, the thickness of the positive active material layer may be 10 μm to 500 μm. It should be understood that these are exemplary only, and other suitable thicknesses may be used.

[0117] In some embodiments, as described above, the positive electrode active material layer includes a positive electrode active material. In some embodiments, the positive electrode active material may include at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, or lithium nickel manganese oxide, and the positive electrode active material may be doped and / or coated.

[0118] In some embodiments, the surface of the positive electrode material includes lithium phosphate and / or lithium niobate, the mass ratio of the two is 1:5 to 1:1, and the thickness of the covering layer is 1 μm to 2 μm.

[0119] In some embodiments, the positive electrode active material layer also includes a positive electrode binder and a positive electrode conductor. In some embodiments, the positive electrode binder may include polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, styrene-acrylate copolymer, styrene-butadiene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene. In some embodiments, the positive electrode conductor may include at least one of conductive carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes or carbon fibers.

[0120] In the present application, the electrochemical device includes an electrolyte, and the electrolyte includes a lithium salt and a non-aqueous solvent. The present application has no particular restrictions on the lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to at least one of LiPF6, LiBF4, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalate borate) (LiBOB) or lithium difluoroborate. The present application has no particular restrictions on the content of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the mass of the electrolyte, the mass percentage of the lithium salt is 5% to 23%, for example, the concentration of the lithium salt in the electrolyte can be 5%, 8%, 12%, 16%, 20%, 23% or a range composed of any two of the above values. The present application has no particular restrictions on the non-aqueous solvent, as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of chain carbonate compounds, cyclic carbonate compounds or fluorocarbonate compounds. The above-mentioned chain carbonate compounds may include but are not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (MEC). The above-mentioned cyclic carbonate may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.The present application has no particular limitation on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved.

[0121] In some embodiments, the isolation film includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. In particular, polyethylene and polypropylene have a good effect on preventing short circuits and can improve the safety of the battery through the shutdown effect. In some embodiments, the thickness of the isolation film is in the range of about 3μm to 480μm.

[0122] In some embodiments, the isolation membrane has a porous layer, and the binder of the porous layer is selected from at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene. The porous layer on the surface of the isolation membrane can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the isolation membrane, and enhance the adhesion between the isolation membrane and the pole piece. The diaphragm can also include a high melting point crystalline polymer or a high temperature resistant amorphous polymer, and the high temperature resistant resin includes at least one of polypropylene, poly-4-methylpentene, polytetrafluoroethylene, polyvinylidene fluoride and cycloolefin copolymers. The high melting point crystalline polymer includes at least one of polypropylene, poly-4-methylpentene, polytetrafluoroethylene or polyvinylidene fluoride, and the high temperature resistant amorphous polymer includes cycloolefin copolymers. Based on the mass of the polyolefin porous substrate, the mass percentage Z of the high temperature resistant resin is 2%~10%. For example, the mass percentage Z of the high temperature resistant resin is 2%, 3%, 5%, 7%, 8%, 10% or a range consisting of any two of these values. When the above-mentioned type of high temperature resistant resin is added to the polyolefin porous substrate and the mass percentage of the high temperature resistant resin is controlled within the above range, it is beneficial to increase the melting point of the diaphragm, improve the strength and high temperature performance of the electrochemical device.

[0123] In some embodiments, the electrochemical device is a lithium-ion battery, but the present application is not limited thereto.

[0124] In some embodiments of the present application, taking lithium-ion batteries as an example, the positive electrode sheet, the isolation membrane, and the negative electrode sheet are wound or stacked in sequence to form an electrode assembly, and then placed in a shell such as an aluminum-plastic film for packaging, and the electrolyte is injected, formed, and packaged to make a lithium-ion battery.

[0125] Embodiments of the present application also provide electronic devices including the above-mentioned electrochemical devices. The electronic devices of the embodiments of the present application are not particularly limited, and they can be any electronic devices known in the prior art. In some embodiments, the electronic device can include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0126] Some specific embodiments and comparative examples are listed below to better illustrate the present application, wherein a lithium-ion battery is used as an example.

[0127] Example 1-1 Positive electrode: lithium cobalt oxide, acetylene black and polyvinylidene fluoride are mixed in a weight ratio of 88:6:6 and added into N-methylpyrrolidone, and stirred into a uniform slurry. The slurry is stirred, coated, dried, rolled and spot welded to obtain the positive electrode of the battery.

[0128] Negative electrode: Weigh 100g of negative electrode active material (artificial graphite with a particle size of 10μm), 1g of conductive agent (carbon black), and 4g of binder (styrene-butadiene rubber, SBR) and add them to 3g of N-methylpyrrolidone and 100g of water to form a negative electrode slurry. The negative electrode slurry is stirred, coated, dried, rolled, and spot-welded to the electrode lug to obtain the battery negative electrode.

[0129] Electrolyte: In a glove box filled with argon, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate were mixed in a mass ratio of 3:4:3, and lithium difluorooxalatoborate accounting for 4.5% of the total mass of the electrolyte and propyl propionate accounting for 20% of the total mass of the electrolyte were added. A certain amount of lithium hexafluorophosphate was added so that the final concentration of lithium salt in the electrolyte was 8.5%.

[0130] Isolation film: A 7 μm thick polyethylene (PE, porosity 30%) microporous membrane was selected, and cellulose nanocrystals (diameter: 10 nm, length: 200 nm, Young's modulus: 70 GPa, MAINE) were added to water and dispersed to prepare a dispersion. After the porous polymer substrate was impregnated with the dispersion, it was air-dried at 60 ° C using a hot air gun. The loading amount of cellulose nanocrystals on the porous polymer substrate was 9 g / m 2 . A diaphragm substrate having a thickness of 9 μm was manufactured.

[0131] Boehmite with a D90 of 7µm and a binder polyacrylate are dispersed in deionized water in a mass ratio of 88:12 to form an inorganic coating slurry with a solid content of 38%; the predetermined slurry is coated on both surfaces of the negative electrode circle by gravure roller coating at a speed of 0.6m / min, and is dried by blowing hot air at 120°C at a wind speed of 0.5m / sec, thereby forming a second coating with a thickness of 2μm adhered to the surface of the PE substrate.

[0132] Organic coating preparation (coated on the second coating on the side facing the negative electrode): Add polymer particles of a first polymer with a melt index of 10g / 10min and a polymer particle of a second polymer with a melt index of 2g / 10min and a base monomer of vinylidene fluoride into a stirrer at a molar ratio of 1:1 and stir evenly; add sodium carboxymethyl cellulose into the stirrer and stir evenly; add dimethylsiloxane as a wetting agent into the stirrer, and then add deionized water and stir to adjust the viscosity of the slurry to 38mPa•s and the solid content to 5% to obtain an organic coating slurry. The organic coating slurry is evenly applied to the second coating layer (the isolation membrane on the side facing the anode / negative electrode), and after drying in an oven, the first coating layer is obtained. The coating weight of the first coating slurry is 1.5mg / 5000mm 2 The thickness of the first coating layer is 3 μm. The mass ratio of the first polymer, the second polymer, sodium carboxymethyl cellulose, and dimethyl siloxane is 75:20:0.7:4.3.

[0133] Preparation of polydopamine coating (first coating) (coated on the second coating facing the positive electrode side) Dopamine at a concentration of 2 mg / mL and dextrin at a concentration of 50 mg / mL were added to an alkaline buffer solution (20 mM Tris-HCl buffer) at room temperature (25°C), and the final content of dopamine and dextrin was adjusted to 1:2 by adding the amount, and then the lid of the petri dish was opened to prepare a dopamine and dextrin solution having a dissolved oxygen content of 8 ppm and a pH of 8. The pre-separated membrane was immersed in the solution for 48 hours and then dried at 60°C for 15 hours to have a total thickness of 15 μm (the thickness of the remaining part of the isolation membrane was 13 μm, and the thickness of the polydopamine coating was 2 μm), preparing a separator containing polydopamine and dextrin at a weight ratio of 1:2.

[0134] Preparation of negative electrode sheet: artificial graphite, conductive carbon black, styrene-butadiene rubber (SBR), and sodium carboxymethyl cellulose (CMC) are mixed at a weight ratio of 97:1:1:1, deionized water is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 80wt%. The negative electrode slurry is evenly coated on one side of the negative electrode current collector copper foil, and dried at 110°C to obtain a negative electrode sheet coated with a negative electrode active material layer with a thickness of 90μm on one side. The above steps are repeated on the other side of the negative electrode current collector copper foil to obtain a negative electrode sheet coated with a negative electrode active material layer on both sides. After cold pressing, cutting, and slitting, a negative electrode sheet with a specification of 476mm×93.5mm is obtained, and the surface resistance of the negative electrode sheet is tested to be 0.002mΩ / cm 2 .

[0135] Preparation of lithium-ion batteries: stack the positive electrode sheet lithium iron phosphate, the isolation membrane, and the negative electrode sheet silicon carbon negative electrode in order, so that the isolation membrane is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and wind them to obtain an electrode assembly. After welding the pole ears, place the electrode assembly in an outer packaging aluminum-plastic film, remove moisture at 80°C, inject the above-mentioned electrolyte, and undergo vacuum packaging, standing, formation, shaping, capacity testing and other processes to obtain a lithium-ion battery.

[0136] The test method is as follows: (1) Low-temperature fast charging test method: At -10°C, the lithium-ion batteries prepared in the examples and comparative examples were subjected to constant current charging tests at a rate of 2C, and their rate charging capacity retention rates were calculated. The battery's rate charging retention rate at 2C = the capacity discharged after charging at a rate of 2C / the capacity discharged after charging at a rate of 0.5C.

[0137] (2) High temperature interval cycle test: Place the battery in a (50±3)℃ environment and let it stand for 3 hours. When the battery cell reaches (50±3)℃, charge the battery to 4.25V at a constant current of 1C. Charge the battery to a cut-off current of 0.05C at a constant voltage of 4.25V. Let it stand at (50±3)℃ for a certain period of time to ensure that the constant current and constant voltage charging time plus the standing time is 24 hours. Then discharge the battery at 0.5C and record the initial energy E0. Repeat this cycle. When the cycle reaches the required number of times, use the discharge energy as the battery's energy E1 and calculate the energy retention rate (%), where energy retention rate (%) = E1 / E0 × 100%.

[0138] (3) Overcharge test pass rate: At (45±5)℃, the discharged battery cell is charged at 3.5C constant current to 5.0V, then changed to constant voltage charging. The charging time is limited to 6 hours or the charging is stopped when the battery surface temperature is stable (temperature difference within 30min ≤2℃). Judgment standard: The battery cell does not catch fire. Each embodiment is tested with 5 parallel samples as a group.

[0139] (4) Overcurrent safety test: At room temperature of 25°C, the secondary battery is charged at a constant current of 1C from 10% to 30% of the battery state of charge (SOC). Then, the secondary battery is charged at a constant current of 1.5C from 30% to 60% of the battery state of charge (SOC). Then, the secondary battery is charged at a constant current of 2C from 60% to 90% of the battery state of charge (SOC). The temperature of the secondary battery is then monitored with a temperature measuring instrument.

[0140] The lower the temperature of the secondary battery measured above, the better the performance of the secondary battery. The secondary battery is graded (A to D) according to the test results of the temperature, and the grading criteria are as follows: A: Temperature is less than 50℃; B: The temperature is above 50℃ and below 55℃; C: The temperature is above 55℃ and below 60℃; D: Temperature greater than 60°C.

[0141] The samples rated A have passed the overcurrent safety test, and each embodiment / comparative example has 20 parallel samples to calculate the test pass rate.

[0142] (5) Side squeeze test: At 25°C, charge at a constant current of 0.5C to 4.4V, and then charge at a constant voltage of 0.05C. Adopt the UL1642 test standard, and the side squeeze force is 13kN. Perform side squeeze test on lithium-ion secondary batteries, test 20 lithium-ion secondary batteries in each group, and calculate the pass rate of side squeeze test of lithium-ion secondary batteries.

[0143] (6) Drop test pass rate: Under the environmental condition of 25℃, record the open circuit voltage and internal resistance of the battery (the test instrument is a voltage resistance tester, manufacturer: Dongguan Lijia Precision Instrument Co., Ltd., model: LNG-SY1-0020-DQ); put the battery into the fixture bin, and use the automatic drop device to drop the fixture bin with the battery from a position of 1m to the cement bottom plate in the manner of landing on the bottom surface, left side, right side, back side, front side and top side of the fixture bin head in a round. One cycle is a total of 3 rounds, i.e. 18 times; then drop the battery to the cement bottom plate in the order of landing on the bottom surface, left side, right side, back side, front side and top side of the fixture bin head in the order of landing on the cement bottom plate in the order of landing on the bottom surface, left side, right side, back side, front side and top side of the fixture bin head in the order of landing on the cement bottom plate in the order of landing on the bottom surface, left side, right side, back side, front side and top side of the fixture bin head in the order of landing on the top surface ... The bottom, left, right, back, front and top of the fixture are dropped from a position of 1.5m to the cement floor in a round of landing. A total of 3 rounds of drops, or 18 times, are performed in one cycle. The voltage of the battery is measured after each round of drops. If the battery catches fire or leaks, the drop is stopped, otherwise it continues to drop. The voltage and internal resistance of the battery are recorded. If the voltage drop is <10mV within 24 hours and the battery packaging bag is not opened or broken, and the battery does not catch fire, leak or explode, the battery is judged to have passed the drop test, otherwise it is considered to have failed. Drop test pass rate (%) = (number of products that passed the drop test ÷ total number of products participating in the drop test) × 100%.

[0144] (7) Electrolyte component testing: GC-MS was used to test the electrolyte components in combination with the external standard method.

[0145] (8) Young's modulus test: Wash off the coating on the diaphragm, cut the substrate sample into a rectangle with a length of 120 mm and a width of 10 mm as the experimental sample. Adjust the direction so that the length of the diaphragm in the MD direction is 120 mm. Use a tensile tester (which can be a Strograph R-3 manufactured by Toyo Seiki Seisaku-sho or other tensile testers that can be used to test the Young's modulus) to perform a tensile test in the MD direction of the diaphragm. The initial distance between the chucks is 50 mm and the tensile speed is 500 mm / min. The Young's modulus is calculated by the tensile load at 1% elongation and the cross-sectional area of ​​the sample by tensile load (1% elongation) / cross-sectional area × 100. The results of each example / comparative example are obtained by measuring three parallel experimental samples and taking the average value.

[0146] (9) Substrate smoothness test: The surface gloss (GU value) was measured at a reflection angle of 60° using “micro-TRI-gloss-s” manufactured by BYK.

[0147] Examples 1-2 to 1-33 and Comparative Examples 1-1 to 1-2 The preparation of the lithium-ion battery is roughly the same as that of Example 1-1, with the only difference being the Young's modulus X of the base film, the polydopamine content A in the first coating, the mass ratio A / B of polydopamine to dextrin, the thickness C, A / C of the first coating, the surface gloss E of the base film, the size D, C / D of the D90 of the particles in the second coating, the electrode bonding strength T and X / T between the separator and the negative electrode sheet. The specific parameters are shown in Table 1.

[0148] Table 1 Table 1 According to Table 1, the low-temperature fast charge cycle retention rate, high-temperature intermittent cycle retention rate and drop test pass rate of the lithium-ion battery in each embodiment are significantly improved compared with the comparative example. When the first coating of the isolation film includes polydopamine and the Young's modulus of the base film of the isolation film meets the range of this application, the lithium-ion battery has good low-temperature performance, high-temperature performance and structural stability.

[0149] According to Examples 1-2, 1-3 and 1-33, the Young's modulus of the base film is 55≤X≤70, and the low-temperature performance and high-temperature performance of the lithium-ion battery are better.

[0150] According to Examples 1-2, 1-6 to 1-8, and 1-23 to 1-24, the thickness of the first coating layer of the isolation membrane satisfies 1≤C≤4, and the lithium-ion battery has better low-temperature performance, high-temperature performance and structural stability.

[0151] According to Examples 1-2 and 1-9 to 1-16, the mass ratio A / B of polydopamine to dextrin in the first coating of the isolation membrane is 0.02-2, and the lithium-ion battery has good low-temperature performance, high-temperature performance and structural stability.

[0152] According to Examples 1-2, 1-21 to 1-22, and 1-31 to 1-32, the surface glossiness of the base film of the isolation film satisfies 1≤E≤5.5, and the lithium-ion battery has better low-temperature performance, high-temperature performance and structural stability.

[0153] According to Examples 1-2, 1-17 to 1-20, and 1-29 to 1-30, the D90 of the particles in the second coating of the isolation membrane satisfies 0.6 μm ≤ D ≤ 10 μm, and the lithium-ion battery has better low-temperature performance, high-temperature performance and structural stability.

[0154] On this basis, according to Examples 1-17 to 1-19, the D90 of the particles in the second coating of the isolation membrane satisfies 0.6 μm≤D≤5 μm, and the lithium-ion battery has better low-temperature performance, high-temperature performance and structural stability.

[0155] On this basis, according to Examples 1-17 to 1-19, the D90 of the particles in the second coating of the isolation membrane satisfies 0.6 μm≤D≤5 μm, and the lithium-ion battery has better high temperature performance and structural stability.

[0156] Example 2-1 to Example 2-12 The preparation of the lithium-ion battery is substantially the same as that of Example 1-1, except that the average molecular weight, melting point or porosity of the first coating of polydopamine is different. The specific parameters are shown in Table 2.

[0157] Table 2 According to Table 2, when the average molecular weight of polydopamine is 120KDa~900KDa, the melting point of polydopamine is 160℃~220℃ or the porosity of the first coating is 30%~65%, the lithium-ion battery of the present application has good side extrusion test pass rate, overcurrent safety test pass rate, overcharge test pass rate and low-temperature fast charging cycle retention rate.

[0158] According to Example 1-1, Example 2-1 to Example 2-4, Example 2-9, and Example 2-10, when the average molecular weight of polydopamine is 120KDa~900KDa and / or the melting point of polydopamine is 160℃~220℃, the lithium-ion battery has better structural stability, charging stability and low temperature performance.

[0159] According to Example 1-1, Example 2-5 to Example 2-8, Example 2-11, and Example 2-12, when the porosity of the first coating is 30% to 65%, the lithium-ion battery has better structural stability, charging stability, and low-temperature performance.

[0160] Example 3-1 to Example 3-34 The preparation of the lithium-ion battery is substantially the same as that of Example 1-1, except that the contents of propyl propionate, lithium bis(fluorooxalatoborate), lithium bis(fluorosulfonyl)imide, 1,3-propane sultone, vinyl ethylene carbonate, vinyl sulfate and 1,2,3-tris(2-cyano)propane in the electrolyte are different. The specific parameters are shown in Table 3.

[0161] Table 3 Table 3 According to Table 3, when the electrolyte includes propyl propionate, lithium bis(fluorooxalatoborate), lithium bis(fluorosulfonyl)imide, 1,3-propanesultone, vinyl ethylene carbonate, vinyl sulfate and 1,2,3-tris(2-cyano)propane, the lithium-ion battery of the present application has good side extrusion test pass rate, overcurrent safety test pass rate, overcharge test pass rate and low-temperature fast charge cycle retention rate.

[0162] According to Example 1-1, Example 3-1 to Example 3-3, Example 3-26, and Example 3-27, when the content of propyl propionate in the electrolyte satisfies 20≤G≤45, the lithium-ion battery has better structural stability, charging stability and low temperature performance.

[0163] According to Example 1-1, Example 3-1 to Example 3-3, Example 3-34, and Example 3-35, lithium bis(fluorosulfonyl)imide and propyl propionate in the electrolyte satisfy 0.02≤H / G≤0.48, and the lithium ion battery has better structural stability, charging stability and low temperature performance.

[0164] On this basis, according to Example 1-1, Example 3-1, and Example 3-2, lithium bis(fluorosulfonyl)imide and propyl propionate in the electrolyte satisfy 0.02≤H / G≤0.3, and the lithium-ion battery has better structural stability, charging stability, and low temperature performance.

[0165] According to Example 3-1, Example 3-4 to Example 3-8, and Example 3-28, when the content of lithium difluorooxalate borate in the electrolyte satisfies 0.01≤F≤4.5, the lithium ion battery has better structural stability, charging stability and low temperature performance.

[0166] According to Example 3-1, Example 3-9 to Example 3-13, Example 3-29, and Example 3-30, when the content of 1,3-propane sultone in the electrolyte satisfies 0.2≤I≤3.5, the lithium-ion battery has better structural stability, charging stability and low temperature performance.

[0167] On this basis, according to Examples 3-1, 3-9 to 3-11, when the content of 1,3-propane sultone in the electrolyte satisfies 0.2≤I≤2, the lithium-ion battery has better structural stability, charging stability and low temperature performance.

[0168] According to Example 3-1, Example 3-14 to Example 3-17, and Example 3-31, when the content of vinyl ethylene carbonate in the electrolyte satisfies 0.1≤J≤3.5, the lithium-ion battery has better structural stability, charging stability and low-temperature performance.

[0169] On this basis, according to Examples 3-1, 3-12 to 3-14, when the content of vinyl ethylene carbonate in the electrolyte satisfies 0.1≤J≤1.8, the lithium-ion battery has better structural stability, charging stability and low temperature performance.

[0170] According to Example 3-1, Example 3-18 to Example 3-21, and Example 3-32, when the content of vinyl sulfate in the electrolyte satisfies 0.1≤K≤3.5, the lithium-ion battery has better structural stability, charging stability and low-temperature performance.

[0171] On this basis, according to Examples 3-1, 3-18 to 3-20, when the content of vinyl sulfate in the electrolyte satisfies 0.1≤K≤2.5, the lithium-ion battery has better structural stability, charging stability and low temperature performance.

[0172] According to Example 3-1, Example 3-22 to Example 3-25, and Example 3-33, when the content of 1,2,3-tris(2-cyano)propane in the electrolyte satisfies 0.1≤L≤2.8, the lithium-ion battery has better structural stability, charging stability and low temperature performance.

[0173] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present application. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there is no structural conflict. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A separation film, characterized in that: The isolation film includes a base film and a first coating layer disposed on at least one side of the base film, the first coating layer includes polydopamine and an adhesive polymer, and the Young's modulus of the base film is 52 MPa to 90 MPa.

2. The isolation film according to claim 1, characterized in that: The Young's modulus of the base film is 55MPa~70MPa.

3. The isolation film according to claim 1, characterized in that: The polydopamine satisfies at least one of the following: (1) The average molecular weight of the polydopamine is 120KDa~900KDa; (2) The melting point of the polydopamine is 160°C to 220°C.

4. The isolation film according to claim 1, characterized in that: The first coating layer further comprises inorganic ceramic particles, and / or the binder polymer comprises dextrin.

5. The isolation film according to claim 1, characterized in that: The adhesive polymer includes dextrin. Based on the total mass of the first coating, the mass percentage of polydopamine in the first coating is Awt%, the mass percentage of dextrin in the first coating is Bwt%, and the isolation film satisfies: 0.02≤A / B≤2.

6. The isolation film according to claim 1, characterized in that: The isolation film further includes a second coating layer, wherein the second coating layer is disposed on both sides of the base film, the first coating layer is disposed on at least one side outside the second coating layer, and the D90 of particles in the second coating layer is 0.6 μm to 10 μm.

7. The isolation film according to claim 6, characterized in that: The D90 of the particles in the second coating layer is 0.6 μm to 5 μm.

8. The isolation film according to claim 1, characterized in that: The isolation film also includes a second coating, which is arranged on both sides of the base film, and the first coating is arranged on at least one side outside the second coating. The thickness of the first coating is Cμm, the D90 of the particles in the second coating is Dμm, and the isolation film satisfies: 0.06≤C / D≤10.

9. The isolation film according to claim 8, characterized in that: The isolation film satisfies: 0.2≤C / D≤7.

10. The isolation film according to any one of claims 1 to 9, characterized in that: The first coating satisfies at least one of the following: (1) The thickness of the first coating is 1 μm to 4 μm; (2) The porosity of the first coating is 30% to 65%; (3) The surface glossiness of the base film is 1GU~5.5GU; (4) Based on the total mass of the first coating layer, the mass percentage of the polydopamine in the first coating layer is Awt%, the thickness of the first coating layer is Cμm, and the isolation film satisfies: 0.25≤A / C≤67.

11. An electrochemical device, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator as described in any one of claims 1 to 10, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the electrolyte comprises a lithium salt and a non-aqueous solvent.

12. The electrochemical device according to claim 11, characterized in that The electrolyte satisfies at least one of the following: (1) The lithium salt comprises at least one of lithium bis(trifluoromethylsulfonyl)imide and lithium difluorophosphate, and the mass percentage of lithium bis(trifluoromethylsulfonyl)imide or lithium difluorophosphate in the electrolyte is 0.01wt% to 4.5wt% based on the total mass of the electrolyte; (2) The lithium salt comprises at least one of lithium bis(trifluoromethylsulfonyl)imide and lithium difluorophosphate; based on the total mass of the electrolyte, the mass percentage of lithium bis(trifluoromethylsulfonyl)imide or lithium difluorophosphate in the electrolyte is Fwt%; based on the total mass of the first coating, the mass percentage of polydopamine in the first coating is Awt%; and the electrochemical device satisfies: 6≤A / F≤3330; (3) The non-aqueous solvent includes propyl propionate, and the mass percentage of the propyl propionate in the electrolyte is 20wt%~45wt% based on the total mass of the electrolyte.

13. The electrochemical device according to claim 11, characterized in that The non-aqueous solvent includes propyl propionate, and the lithium salt includes lithium bis(fluorosulfonyl)imide; based on the total mass of the electrolyte, the mass percentage of propyl propionate in the electrolyte is Gwt%, the mass percentage of lithium bis(fluorosulfonyl)imide is Hwt%, and the electrochemical device satisfies: 0.02≤H / G≤0.

48.

14. The electrochemical device according to claim 13, characterized in that The electrochemical device satisfies: 0.02≤H / G≤0.

3.

15. The electrochemical device according to claim 11, characterized in that The electrolyte further includes an additive, wherein the additive includes at least one of 1,3-propane sultone, vinyl ethylene carbonate, vinyl sulfate, and 1,2,3-tris(2-cyano)propane.

16. The electrochemical device according to claim 15, characterized in that The electrochemical device satisfies at least one of the following: (1) The additive includes 1,3-propane sultone, and the mass percentage of the 1,3-propane sultone in the electrolyte is 0.2wt%~3.5wt% based on the total mass of the electrolyte; (2) The additive includes vinyl ethylene carbonate, and the mass percentage of the vinyl ethylene carbonate in the electrolyte is 0.1wt%~3.5wt% based on the total mass of the electrolyte; (3) The additive includes vinyl sulfate, and the mass percentage of the vinyl sulfate in the electrolyte is 0.1wt%~3.5wt% based on the total mass of the electrolyte; (4) The additive includes 1,2,3-tris(2-cyanato)propane, and the mass percentage of the 1,2,3-tris(2-cyanato)propane in the electrolyte is 0.1wt%~2.8wt% based on the total mass of the electrolyte; (5) The additive includes 1,3-propane sultone. Based on the total mass of the electrolyte, the mass percentage of the 1,3-propane sultone is 1wt%. Based on the total mass of the first coating, the mass percentage of the polydopamine in the first coating is Awt%. The electrochemical device satisfies: 8≤A / I≤334.

17. The electrochemical device according to claim 16, characterized in that The electrochemical device satisfies at least one of the following: (1) The additive includes 1,3-propane sultone, and the mass percentage of the 1,3-propane sultone is 0.2wt%~2wt% based on the total mass of the electrolyte; (2) The additive includes vinyl ethylene carbonate, and the mass percentage of the vinyl ethylene carbonate is 0.1wt% to 1.8wt% based on the total mass of the electrolyte; (3) The additive includes vinyl sulfate, and the mass percentage of the vinyl sulfate is 0.1wt%~2.5wt% based on the total mass of the electrolyte.

18. The electrochemical device according to claim 11, characterized in that The electrode bonding strength between the isolation film and the negative electrode plate is 1.8 gf / 15 mm to 3.6 gf / 15 mm.

19. The electrochemical device according to claim 11, characterized in that The Young's modulus of the base film is XMPa, the electrode bonding strength between the isolation film and the negative electrode plate is Tgf / 15mm, and the electrochemical device satisfies: 15≤X / T≤43.

20. An electronic device, characterized in that: An electrochemical device comprising any one of claims 11 to 19.

Citation Information

Patent Citations

  • Isolation membrane and lithium ion battery containing same

    CN108023051A

  • Flexible lithium battery diaphragm

    CN112635919A

  • Separator for electrochemical device, method for manufacturing same, and electrochemical device comprising same

    CN118947019A

  • Electrolyte, electrochemical device and electronic device

    CN119170869A

Cited By

  • Separator, electrochemical device and electronic device

    WO2026175153A1